Effect of Phoenix dactylifera on Changes in Placental Growth Rate Factors in Pregnant Women - Husaidah, Siti; Amru, Desi Ernita; Heroyanto, Heroyanto (Papua Medicine and Health Science, 2025)
The annual maternal mortality rate (MMR) fluctuates and one of the causes is preeclampsia with 33.3% of the incidence of preeclampsia and maternal mortality. Placental growth factor (PlGF) has a major role in the development of preeclampsia. Objective: Analyzing the Effect of Phoenix Dactylifera on Changes in Levels of Placental Growth Factor (PlGF) as a predictor of preeclampsia in pregnant women. Method: This research uses a hybrid method, which combines two research methods (Quasy Experiment and Prospective Khohort) with a pre-post test control design. A total of 40 respondents (30 respondents in the ajwa date group and 10 respondents in the group recommended to eat fruits and vegetables) the sample size was determined using the Yamane formula with simple random sampling technique. Data analysis using the Wilcoxon test. Results: The Wilcoxon test on changes in PLGF levels based on the pre-post test intervention group produced the Asymp value. Sig 0.000 <0.05 (Mean: 0.591-3.856) and the control group pre-post test resulted in Asymp values. Sig 0.073> 0.05 (Mean: 1.040-0.701). Conclusion: The changes that occurred in the intervention group were due to a significant decrease in blood pressure which affected PLGF levels in blood plasma after giving phoenix dactylifera fruit for 8 weeks and given 7 eggs / day (100 grams). Phoenix dactylifera can inhibit the development of PlGF in blood plasma thus preventing the occurrence of preeclampsia in pregnant women who are hypertensive.